2016
DOI: 10.1016/j.jjcc.2015.08.013
|View full text |Cite
|
Sign up to set email alerts
|

Left atrial remodeling, early repolarization pattern, and inflammatory cytokines in professional soccer players

Abstract: Athletes with an ER pattern had significantly higher E/e' ratios, reflecting higher atrial filling pressures, higher LA volume, and higher IL-6 plasma levels. All these factors may contribute to atrial remodeling over time and thus increase the risk of AF in long-term endurance sports.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
8
3
6

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 39 publications
5
8
3
6
Order By: Relevance
“…It has previously been reported that increased E/e 0 as seen in adult athletes reflected higher atrial filling pressures and higher LA volume which may contribute to atrial remodelling over time and thus also increase the risk of atrial fibrillation (Stumpf et al, 2016). This is in line with the increase in LA total strain and LV a 0 immediately after exercise which suggests that atrial function is enhanced and important in the response to exercise.…”
Section: Linear Regressionsupporting
confidence: 61%
See 1 more Smart Citation
“…It has previously been reported that increased E/e 0 as seen in adult athletes reflected higher atrial filling pressures and higher LA volume which may contribute to atrial remodelling over time and thus also increase the risk of atrial fibrillation (Stumpf et al, 2016). This is in line with the increase in LA total strain and LV a 0 immediately after exercise which suggests that atrial function is enhanced and important in the response to exercise.…”
Section: Linear Regressionsupporting
confidence: 61%
“…Further, we confirmed that exercise-induced E/e 0 enhancement is not unique to endurance-trained adolescents, as similar patterns were found in both groups. It has previously been reported that increased E/e 0 as seen in adult athletes reflected higher atrial filling pressures and higher LA volume which may contribute to atrial remodelling over time and thus also increase the risk of atrial fibrillation (Stumpf et al, 2016). Mutual comparison between the groups in our study showed that the active group had higher E/e 0 both immediately and 15 min after ended exercise compared with the controls.…”
Section: Linear Regressionsupporting
confidence: 54%
“…47 Atrial dilatation. Left atrial size is a risk factor for atrial fibrillation, 56 and cross-sectional studies show enlargements of the left atrium in athletes, 14,46,[57][58][59][60][61][62][63] which is also shown in experimental animal models. 64 Longitudinal studies confirm left atrial remodelling after a period of high-volume exercise.…”
Section: Potential Mechanisms Explaining An Increased Atrial Fibrillamentioning
confidence: 99%
“…While regular exercise reduces inflammatory markers, long‐term intense exercise may lead to chronic inflammatory states, perhaps via an over‐training syndrome mediated by excess cytokines . Vigorous exercise increases inflammatory factors such as C‐reactive protein (CRP), interleukin‐6 (IL‐6), and tumor necrosis factor‐alpha (TNF‐alpha) . These factors are released by atrial stretch caused by elevated atrial pressure as occurs during vigorous exercise …”
Section: Discussionmentioning
confidence: 99%